The German presidency of the council and the EU social dimension - László Andor (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
On the 1st of July, Germany will take over the rotating presidency of the Council of the European Union. Normally, holding the chair of the council is not something that is considered to be a power position, especially since the Prime Minister of the given country is not chairing the European Council, which has been headed by an elected President since the entry in force of the Lisbon Treaty. However, Germany is taking over the presidency at a critical time which, even without the COVID-19 crisis, would have been a decisive juncture. The COVID-19 crisis and its aftermath allows the German government to play an extraordinary role in shaping the future of the EU, and within that, its social dimension. In this policy brief, we first outline the German approach to "Social Europe" in a historical perspective, and present an overview of the evolution of the EU social dimension itself. This will be followed by a discussion of the key items on the social agenda during the forthcoming German presidency. A schedule of planned Presidency meetings is given in an annex.
urn:nbn:de:101:1-2020071015231918744632
Keywords: 330; EU-Politik; EU-Sozialpolitik; Staatsoberhaupt; EU-Staaten; Deutschland